2017
DOI: 10.1186/s12890-017-0532-1
|View full text |Cite
|
Sign up to set email alerts
|

Plasma surfactant protein-D as a diagnostic biomarker for acute respiratory distress syndrome: validation in US and Korean cohorts

Abstract: BackgroundAcute respiratory distress syndrome (ARDS) is potentially underrecognized by clinicians. Early recognition and subsequent optimal treatment of patients with ARDS may be facilitated by usage of biomarkers. Surfactant protein D (SP-D), a marker of alveolar epithelial injury, has been proposed as a potentially useful biomarker for diagnosis of ARDS in a few studies. We tried to validate the performance of plasma SP-D levels for diagnosis of ARDS.MethodsWe conducted a retrospective analysis using data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 22 publications
(40 reference statements)
2
45
1
3
Order By: Relevance
“…In vitro studies with SP-D showed that it modulates antigen presentation to class II T cells in a dose-dependent manner and plays a role in the clearance of influenza A and HIV viruses [18,19]. Studies related to SARS-CoV demonstrated a strong relationship between mutations in the MBL gene and poor prognosis and clinical course [6,20]. In studies evaluating the relationship between SP-D level and respiratory and non-respiratory diseases, higher levels were observed with chronic airway diseases and smoking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies with SP-D showed that it modulates antigen presentation to class II T cells in a dose-dependent manner and plays a role in the clearance of influenza A and HIV viruses [18,19]. Studies related to SARS-CoV demonstrated a strong relationship between mutations in the MBL gene and poor prognosis and clinical course [6,20]. In studies evaluating the relationship between SP-D level and respiratory and non-respiratory diseases, higher levels were observed with chronic airway diseases and smoking.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins mainly target alveolar macrophages, dendritic cells, and T cells and play an important role in agglutination, opsonization, and modulation. Studies have shown that SP-D levels increase with disease severity and IgG level in patients infected with SARS-CoV, a similar coronavirus responsible for severe acute respiratory syndrome (SARS) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The primary cohort was derived from the WC-BOCI at the NYP/WMC, and the validation cohorts were drawn from the ASAN prospective Registry of Critical Illness and the BWH-RoCI. Protocols for recruitment, data collection, and sample processing have been described previously (22,(34)(35)(36), and further detail can be found in the Supplemental Methods. Briefly, both the WC-BOCI and BWH-RoCI cohorts recruited any patient admitted to the medical ICU, with exclusion for the lack of the ability to provide or the lack of a surrogate to provide informed consent and moribund state.…”
Section: Methodsmentioning
confidence: 99%
“…SP-D and KL-6 are also known to be elevated in ARDS patients [14, 36], but no published reports have compared the biomarker levels according to different ARDS etiologies. Using data from Korea and the USA, Park et al showed that plasma SP-D levels were elevated (median, 20.8 ng/mL; interquartile range, 12.7–38.4 ng/mL) in patients with ARDS mostly due to pneumonia (87.2% of the study population) [37]. Ohnishi et al compared SP-D and KL-6 levels in patients with ILD (including IPF and CVD-associated interstitial pneumonia) with those in patients with bacterial pneumonia and healthy subjects [13].…”
Section: Discussionmentioning
confidence: 99%